Keeping disease-free sweetpotato vines closer to farmers “Kinga Marando” - International Potato Center (2016)
The feasibility of using low cost net tunnels to produce disease-free sweetpotato planting material under farmer-multiplier management was assessed in Tanzania and Uganda. A total of 91 Decentralized Vine Multipliers (DVMs) were identified and supplied with 140 net tunnels. Over 3.6 million cuttings were produced over the three-year period. A virus degeneration study conducted under the project showed that with good agronomic practices multipliers should be able produce clean planting material using the net tunnels. Standards for production of quality planting material were developed in Tanzania and are awaiting ministerial assent.